TAp73/ΔNp73 influences apoptotic response, chemosensitivity and prognosis in hepatocellular carcinoma - Müller-Schilling, Martina; Schilling, Tobias; Lorenz, Katja; Schulze-Bergkamen, Henning; Stremmel, Wolfgang; Krammer, Peter H. (Cell death and differentiation, 2005)
We investigated the mechanisms by which TAp73β and dominant-negative p73 (ΔNp73) regulate apoptosis. TAp73β transactivated the CD95 gene via the p53-binding site in the first intron. In addition, TAp73β induced expression of proapoptotic Bcl-2 family members and led to apoptosis via the mitochondrial pathway. Endogenous TAp73 was upregulated in response to DNA damage by chemotherapeutic drugs. On the contrary, ΔNp73 conferred resistance to chemotherapy. Inhibition of CD95 gene transactivation was one mechanism by which ΔNp73 functionally inactivated the tumor suppressor action of p53 and TAp73β. Concomitantly, ΔNp73 inhibited apoptosis emanating from mitochondria. Thus, ΔNp73 expression in tumors selects against both the death receptor and the mitochondrial apoptosis activity of TAp73β. The importance of these data is evidenced by our finding that upregulation of ΔNp73 in hepatocellular carcinoma patients correlates with reduced survival. Our data indicate that ΔNp73 is an important gene in hepatocarcinogenesis and a relevant prognostic factor.
Gesehen am 04.03.2021